Rancang Bangun Aplikasi Puzzle Tokoh Walisongo Metode Steepest Ascent Hill Climbing Berbasis Android - Khairil Anam; Eko Duwi Prastiyo (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2020)
Game is one of the applications that can improve one's development and thinkingpower. When someone plays the game, it is indirectly required to complete the missionand obstacles in the game. That is why playing games can be said to enhance one'sdevelopment and thinking power. One game that can improve the development of one'sthinking power is a puzzle game. Puzzle is a game that is played in pairs and pairs, soas to produce something that has been determined by a system. This puzzle game isvery popular with children, adolescents, adults and also parents. Stepest Ascent HillClimbing searches based on the best heuristic value. In this case the use of the operatordoes not determine the inventor of the solution. Steepest Ascent Hill Climbing is analgorithm method that is widely used for optimization problems